Interrogating Cultures, Unsettling Identities - Encarnacion Tadem, Teresa S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 22 No 2 (2007): Culture and Identity, 2008)
This issue looks beyond earlier debates on Asian culture that, back then, were essentially built around dichotomies or polar opposites. This is because in recent years culture—Asian culture, in particular, has been widely problematized and contested, especially in light of fundamentalist tendencies and movements in the region and all over the world. Digital and nuclear advancements, transnational migration, and widespread political and social violence and destabilization are just few of the global developments of the twenty-first century that have profoundly reshaped the field. The theme of the issue emphasizes the valuable place of identity, viewed as a social and conceptual construct than an immutable psychological entity. Identity occupies an important place in discourse where cultural ramifications abound; new sites and modes of social interaction often impact on conceptions and perceptions of identity. True to the thrust of Kasarinlan, the articles in this issue also give credence to political economy. In discussions of culture and identity, the articles regard global trends as part of a political, neocolonial and imperialist project, implicitly or otherwise. Each article grounds particular social or ideological issues and the formation of identities within contentious historical or genealogical configurations.
Keywords: culture, identity, cultural studies